2020
DOI: 10.17508/cjfst.2020.12.1.14
|View full text |Cite
|
Sign up to set email alerts
|

Polyphenol content, profile, and distribution in old, traditional apple varieties

Abstract: Apples are an important source of polyphenols in the human diet. They have also shown many potentially beneficial effects on human health. Old, traditional apple varieties grown in the past could also be valuable varieties but little is known about their polyphenolic compounds and characteristics in general. The aim of this study was to collect 25 old, traditional apple varieties, to determine their polyphenolic profile and the amounts of total polyphenols in the peel and flesh, and to compare them with a comm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
0
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 5 publications
2
0
0
Order By: Relevance
“…Traditional apple cultivars had a significantly higher content of procyanidins than conventional ones. Such correlation was also reported by Jakobek et al [34]. Flavonols were also detected in traditional and conventional apple cultivars, specifically quercetine, quercetin-3-ß-D-glucoside, quercetin-3-rutinoside and myricetin (Table 5).…”
Section: Traditionalsupporting
confidence: 85%
“…Traditional apple cultivars had a significantly higher content of procyanidins than conventional ones. Such correlation was also reported by Jakobek et al [34]. Flavonols were also detected in traditional and conventional apple cultivars, specifically quercetine, quercetin-3-ß-D-glucoside, quercetin-3-rutinoside and myricetin (Table 5).…”
Section: Traditionalsupporting
confidence: 85%
“…Phenolic groups detected in pulp had the following order: phenolic acids (8.20-30.8%) > flavan 3-ols (5.10-13.9%) > dihydrochalcones (1.0-1.90%) > flavonol glycosides (0.09-0.40%). The polyphenolic profiles obtained in the present study are in consistence with results reported by other authors [42,43]. Phenolic acids, detected in both peel and pulp, included chlorogenic, caffeic, gallic, protocatechuic, and sinapic acid.…”
Section: Determination Of Polyphenolic Compounds In Applessupporting
confidence: 91%